Pharmacokinetics and Target Attainment of Ceftobiprole in Asian and Non‐Asian Subjects. Issue 7 (16th May 2018) - Muller, A. E.; Punt, N.; Engelhardt, M.; Schmitt‐Hoffmann, A. H.; Mouton, J. W.
Abstract: Ceftobiprole is a broad‐spectrum cephalosporin. The objective of this study was to test the hypothesis that the pharmacokinetics (PK) and exposure of ceftobiprole in Asian subjects are similar to those in non‐Asian subjects. Three approaches were followed. The first compared the individual PK estimates between the 2 subgroups derived from a population PK model previously built. Next, it was determined whether "Asian subject" was a significant covariate. Finally, a pharmacodynamic analysis was performed by comparing measures of exposure and target attainment. No significant differences were found between PK parameter estimates for Asian and non‐Asian subjects, with median values (range) for clearance of 4.82 L/h (2.12–10.47) and 4.97 L/h (0.493–20.6), respectively ( P  = .736). "Asian subject" was not a significant covariate in the population PK model. There were no significant differences between the measures of exposure. The geometric mean ratio for the f AUC was 1.022 (90%CI, 0.91–1.15), indicating bioequivalence. Taking a target of 60% coverage of the dose interval, more than 90% of the population in both subgroups was adequately exposed. This analysis demonstrated that there are no PK or pharmacodynamic differences between Asian and non‐Asian subjects for a ceftobiprole dose of 500 mg every 8 hours as a 2‐hour infusion.